Dextromethorphan Inhibits Activations and Functions in Dendritic Cells. (28th May 2013) - Chen, Der-Yuan; Song, Pei-Shan; Hong, Jau-Shyong; Chu, Ching-Liang; Pan, I-Horng; Chen, Yi-Ming; Lin, Ching-Hsiung; Lin, Sheng-Hao; Lin, Chi-Chen
Abstract : Dendritic cells (DCs) play an important role in connecting innate and adaptive immunity. Thus, DCs have been regarded as a major target for the development of immunomodulators. In this study, we examined the effect of dextromethorphan (DXM), a common cough suppressant with a high safety profile, on the activation and function of DCs. In the presence of DXM, the LPS-induced expression of the costimulatory molecules in murine bone marrow-derived dendritic cells (BMDCs) was significantly suppressed. In addition, DXM treatment reduced the production of reactive oxygen species (ROS), proinflammatory cytokines, and chemokines in maturing BMDCs that were activated by LPS. Therefore, DXM abrogated the ability of LPS-stimulated DCs to induce Ag-specific T-cell activation, as determined by their decreased proliferation and IFN- γ secretion in mixed leukocyte cultures. Moreover, the inhibition of LPS-induced MAPK activation and NF- κ B translocation may contribute to the suppressive effect of DXM on BMDCs. Remarkably, DXM decreased the LPS-induced surface expression of CD80, CD83, and HLA-DR and the secretion of IL-6 and IL-12 in human monocyte-derived dendritic cells (MDDCs). These findings provide a new insight into the impact of DXM treatment on DCs and suggest that DXM has the potential to be used in treating DC-related acute and chronic diseases.